The Marketing Strategy of Saving and Loan Cooperatives in South Tangerang: the Use of SWOT Analysis - Fauziah Septiani; Veta Lidya Delimah Pasaribu; Risza Putri Elburdah; Suharni Rahayu; Krisnaldy (International Journal of Integrative Sciences, 2023)
Marketing strategy is one of many ways to win a sustainable competitive advantage for companies that produce goods or services. Marketing strategy can be viewed as one of the foundations used in compiling a comprehensive company plan. If we perceive such phenomenon from the angle of available problems that exist in companies, it is necessary for companies to have a comprehensive planning in order to be used as a guidance to determine the segments in carrying out their activities. Another reason that shows the importance of compiling a marketing strategy is the fact that generally the competition between companies become tough and tougher these days. This study aims to determine what kind of marketing strategy is implemented in order to achieve the best results that is in accordance with company's product marketing strategy. By conducting a SWOT analysis, i.e. by calculating IFAS and EFAS; the recapitulation results obtained are S-W= a score of 1.5 and O-T = a score of 1.25, these results show that the company's strategy is in quadrant I. Based on the analysis of internal strategic factors that can be seen in SWOT analysis diagram, the position of the saving and loan cooperatives is in quadrant 1 which shows the implementation of SO strategy in the SWOT matrix, namely the aggressive strategy. Aggressive strategy is a strategy that is implemented by using all strengths of the companies in order to take further opportunities. This strategy is a very profitable strategy because it has some opportunities and strengths so that it can be used for the advancement of the Saving and Loan Cooperatives in South Tangerang